Pengaruh Brand Awareness dan Lokasi Terhadap Jumlah Kunjungan Rawat Jalan di Klinik Teratai PKBI Kota Bandung - Rahayu, Novi Kadarini (Green Publisher Indonesia, 2025)
The PKBI Lotus Clinic in Bandung City has a vision of realizing a responsible and inclusive Indonesian society, and its mission is to build an inclusive youth movement and provide general health services, sexual health including HIV/AIDS, and reproductive health in a comprehensive, professional, and inclusive manner. The phenomenon that occurs is that the number of HIV sufferers is increasing, but visits to the PKBI Lotus Clinic in Bandung City have not increased significantly. The purpose of the research is to determine brand awareness, location, and the number of outpatient visits at the PKBI Lotus Clinic in Bandung City, as well as the impact of brand awareness on the number of outpatient visits. The research method uses descriptive and verificative analysis. The results of the descriptive analysis show that brand awareness is in the high to very high category, with the most prominent dimension being brand preference and top of mind. This indicates that the PKBI Lotus Clinic has successfully created awareness. A strong impression in the minds of the public. The location variable is also rated very well by respondents, with high scores in the aspects. The path coefficient analysis using PLS shows that brand awareness has a positive and significant effect on the number of outpatient visits.